Suppression of molten salt corrosion by plasma sprayed Ni3Al coatings - data - Aria, Indrat (Cranfield University, 2021)
Fig. 1 (a) Schematics of air plasma spray deposition of Ni3Al coatings and molten nitrate salt tests at 565 °C. Ni3Alpowder is melted in a stream of plasma at atmospheric pressure and propelled towards the substrate. Each of the SS347 and Ni3Al/SS347 coupons is then immersed in NaNO3: KNO3 salts contained in individual alumina crucibles at a constant temperature of 565 °C for up to 3000 h. (b) Time dependent area-normalised weight change (ΔM/A) of Ni3Al/SS347 and SS347 in molten nitrate saltsand air at 565 °C. Here, the weight change is normalised with the surface area of the coupons. Solid and dashed lines indicate piecewise linear regressions for weight change in molten nitrate salts and air, respectively.Fig. 2 Cross-sectional SEM images of Ni3Al/SS347 (a, b) and SS347 (c, d) at 0 h (a, c) and 3000 h (b, d) of immersion in molten nitrate salt at 565 °C. Dashed lines indicate the interface between Ni3Al coating and SS347 substrate, while arrows indicate AlOx particles embedded within the Ni3Al coatings (a, b). No significant change in the coating morphology and no formation of corrosion layers can be observed on Ni3Al/SS347 after 3000 h. In contrast, formation of corrosion layers can be observed on the surface SS347 after 3000 h. A higher magnification SEM image (inset in d) shows the distinguishable morphologies of these corrosion layers. The dashed line in the inset indicates the interface between the corrosion layers and the original SS347 layer.Fig. 3 (a) Elemental maps and corresponding SEM image ofcross-sectioned Ni3Al/SS347 at 3000 h in molten nitrate salt at 565 °C. These maps show spatial distribution of Fe, Ni, Al, O and Na at the interface between Ni3Al coating and SS347substrate. Arrows indicate AlOx particles embedded within the Ni3Al coatings. All scale bars represent 50 μm. (b) Elemental composition in atomic percentage (at. %) of Fe, Ni, Al, O and Na of Ni3Al/SS347 taken at the area indicated by white line in the corresponding SEM image. The composition is obtained at 3000 h and presented as a function of the distance from the interface between Ni3Alcoating and SS347 substrate. Positive distance corresponds to coatings (Coat) and outer mounting resin (Out), while negative distance corresponds to substrate (Sub). Solid lines are ~ 5-μm simple moving average to guide the eye.Fig. 4 (a) Elemental maps and corresponding SEM imageof cross-sectioned SS347 at 3000 h in molten nitrate saltat 565 °C. These maps show spatial distribution of Fe, Ni,Cr, O and Na at the surface of SS347 substrate. All scale bars represent 50 μm. (b) Elemental composition in atomic percentage (at.%) of Fe, Ni, Cr, O and Na of SS347 taken at the area indicated by white line in the corresponding SEM image. The composition is obtained at 3000 h and presented as a function of the distance from the interface between corrosion layers and SS347 substrate. Positive distance corresponds to corrosion layers (Cor) and outer mounting resin (Out), while negative distance corresponds to substrate (Sub). Solid lines are ~ 5-μm simple moving average to guide the eye.Fig. 5 (a) XRD patterns of Ni3Al/SS347 and SS347 at different molten salt exposure times: 0, 1000, 2000 and3000 h. SS347 exhibits peaks that correspond to austenitic stainless steel (filled circle) and various oxides of Fe, including Fe3O4 and (Cr, Fe)2O3 (filled triangle), Fe2NiO4 (filled star) and NaFe2O3 (filled x mark). Ni3Al/SS347 exhibits peaks that corresponds to Ni3Al (filled diamond) and NiO (filled inverted triangle). Peaks are identified according to the International Centre for Diffraction Data (ICDD) database [31, 33, 56–61] (b) Schematic of corrosion suppression of Ni3Al coatings to the SS347 substrate in molten salts. Ni3Al coatings are rapidly oxidised and stabilised in the first 500 h. The formation of oxides within the Ni3Al coatings supresses the diffusion of Na from the molten salt or the release of Fe, Ni and Cr from the substrate for at least 3000 h. In contrast, continuous uptake of O and Na along with the release of Fe, Ni and Cr resulting in the formation of corrosion layers comprised various oxides of iron on the AQ3 surface of SS347.
Keywords: 'Molten nitrate salts'; 'Stainless steel corrosion'; 'Ni3Al coatings'; 'Air plasma spray'; 'Corrosion resistant coatings'; 'Metals and Alloy Materials'; 'Chemical Characterisation of Materials'; 'Synthesis of Materials'; 'Functional Materials'